Comparative analysis of RNAi screening technologies at genome-scale reveals an inherent processing inefficiency of the plasmid-based shRNA hairpin - Bhinder, Bhavneet (2014)
RNAi screening in combination with the genome-sequencing projects would constitute the Holy Grail of modern genetics; enabling discovery and validation towards a better understanding of fundamental biology leading to novel targets to combat disease. Hit discordance at inter-screen level together with the lack of reproducibility is emerging as the technology's main pitfalls. To examine some of the underlining factors leading to such discrepancies, we reasoned that perhaps there is an inherent difference in knockdown efficiency of the various RNAi technologies. For this purpose, we utilized the two most popular ones, chemically synthesized siRNA duplex and plasmid-based shRNA hairpin, in order to perform a head to head comparison. Using a previously developed gain-of-function assay probing modulators of the miRNA biogenesis pathway, we first executed on a siRNA screen against the Silencer Select V4.0 library (AMB) nominating 1,273, followed by an shRNA screen against the TRC1 library (TRC1) nominating 497 gene candidates. We observed a poor overlap of only 29 hits given that there are 15,068 overlapping genes between the two libraries; with DROSHA as the only common hit out of the seven known core miRNA biogenesis genes. Distinct genes interacting with the same biogenesis regulators were observed in both screens, with a dismal cross-network overlap of only 3 genes (DROSHA, TGFBR1, and DIS3). Taken together, our study demonstrates differential knockdown activities between the two technologies, possibly due to the inefficient intracellular processing and potential cell-type specificity determinants in generating intended targeting sequences for the plasmid-based shRNA hairpins; and suggests this observed inefficiency as potential culprit in addressing the lack of reproducibility.